Dipolar dark matter simulations on galaxy scales with the ramses code. Issue 1 (24th September 2022) - Stahl, Clément; Famaey, Benoit; Thomas, Guillaume; Dubois, Yohan; Ibata, Rodrigo
Abstract: We numerically explore on galaxy scales the dipolar dark matter (DM) model based on the concept of gravitational polarization. This DM model has been proposed as a natural way to reproduce observed tight galactic scaling relations such as the baryonic Tully–Fisher relation and the Radial Acceleration Relation. We present a customized version of the RAMSES code including for the first time the dynamics of this Dipolar DM in N -body simulations. As a first application of this code, we check that we recover an equilibrium configuration that had been found analytically, where a low density Dipolar DM halo is at rest with respect to its central galaxy, recovering the aforementioned scaling relations. A characteristic signature of this equilibrium model is that it harbours a dynamical instability with a characteristic time depending on the Dipolar DM halo density, which we recover numerically. This represents a first step towards more involved simulations needed to test this framework, ranging from galaxy interactions to structure formation.